Psychological Assistance for Wives of Victims of Domestic Violence At UPTD PPA Surabaya City as A Form of Empowering Victims - Tara Nabila Maura Diva; Siti Jaro’ah (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Domestic violence is a recurring social problem that negatively impacts the psychological and emotional well-being of its victims, especially women. This study explores the effectiveness of psychological assistance services provided by UPTD PPA Surabaya in helping women victims, particularly wives, recover and achieve self-empowerment. Employing qualitative methods, including interviews, field observations, and document analysis, this research examines a single client case and draws insights from three counsellors. The results reveal that victims often experience psychological downturns, such as low self-esteem and helplessness, which are exacerbated by emotional and financial dependence. UPTD PPA plays a vital role in providing psychological counselling, legal services, and empowerment programs to help victims rebuild their self-confidence and regain autonomy. However, challenges such as limited human resources, societal stigma, and institutional barriers remain. This study concludes that a trauma-informed and empowerment-based approach is essential in supporting the long-term recovery of domestic violence survivors and must be supported by coordinated efforts across community, institutional, and policy levels.